(untitled) (Research, Society and Development, 2022)
Workers offer their knowledge, skills and attitudes to companies, that is, they make their workforce available in exchange for rewards, providing the dynamism and progress of activities in the organizational environment. The involvement and cooperation of everyone in the processes is crucial, it is up to the personnel department sector to act as an integrating element in the employee versus employer relationship; conduct these relationships within the company’s principles, values, vision and mission; meet the requirements of the law, complying with labor procedural legislation and the rules of the social security system. This present work aims to analyze, understand and demonstrate the personnel department sector working with people management, clarifying its importance in decision-making, maintenance and retention of intellectual capital in the organizational environment.